2003
DOI: 10.1210/jc.2002-021827
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Placebo-Controlled Trial of Androgen Effects on Muscle and Bone in Men Requiring Long-Term Systemic Glucocorticoid Treatment

Abstract: Long-term glucocorticoid therapy in men is associated with loss of bone and muscle mass as well as a decrease in serum testosterone. We tested the effect of two androgens, testosterone and its minimally aromatizable analog nandrolone, on muscle mass (dual x-ray absorptiometry), muscle strength (knee flexion and extension by isokinetic dynamometry), bone mineral density (BMD), and quality of life (Qualeffo-41 questionnaire) in 51 men on a mean daily prednisone dose of 12.6 +/- 2.2 mg. Men were randomized, doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(142 citation statements)
references
References 79 publications
(64 reference statements)
7
129
0
6
Order By: Relevance
“…Hormone replacement therapy: glucocorticoids reduce the production of sex hormones. As such, it appears rationale to replace sex hormones in women with amenorrhea and estrogen deficiency (hypothalamic amenorrhea or primary ovarian insufficiency) or in men with proven hypogonadism (31,32). While estrogen therapy is no longer considered a first line therapy for the prevention of postmenopausal osteoporosis, it appears reasonable -in the absence of contraindications -to consider hormone replacement therapy in premenopausal women with estrogen deficiency or in men with hypogonadism treated with glucocorticoids, even if controlled studies on the incidence of fractures are lacking (Grade A recommendation).…”
Section: Calcium and Vitamin Dmentioning
confidence: 99%
“…Hormone replacement therapy: glucocorticoids reduce the production of sex hormones. As such, it appears rationale to replace sex hormones in women with amenorrhea and estrogen deficiency (hypothalamic amenorrhea or primary ovarian insufficiency) or in men with proven hypogonadism (31,32). While estrogen therapy is no longer considered a first line therapy for the prevention of postmenopausal osteoporosis, it appears reasonable -in the absence of contraindications -to consider hormone replacement therapy in premenopausal women with estrogen deficiency or in men with hypogonadism treated with glucocorticoids, even if controlled studies on the incidence of fractures are lacking (Grade A recommendation).…”
Section: Calcium and Vitamin Dmentioning
confidence: 99%
“…Glucocorticoid receptor Glucocorticoid hormones have profound effects on metabolism and cellular proliferation. In skeletal muscle glucocorticoids have catabolic effects on muscle (Crawford et al 2003). The actions of glucocorticoids on muscle are mediated through the glucocorticoid receptor (GR) (Chen et al 1997).…”
Section: Insulin-like Growth Factor-imentioning
confidence: 99%
“…In humans, androgen treatment increased muscle mass in men with muscle wasting due to long-term glucocorticoid therapy (Crawford et al 2003). Androgen therapy in COPD patients who are on glucocorticoid treatment can partly reverse muscle wasting (Creutzberg & Schols 1999, Creutzberg et al 2003.…”
Section: Insulin-like Growth Factor-imentioning
confidence: 99%
“…In fact, a long-term study, performed over 3 years and providing physiologic testosterone levels, did not reveal any difference in respiratory disturbance index compared with the placebo-treated group [90]. Other studies have demonstrated no change in upper airway caliber with high-dose testosterone [58], no development of OSA symtomatology with TRT versus placebo [91], and no effect of testosterone blockade on nocturnal breathing or chemosensitivity in OSA patients [92]. Santamarie and colleagues even demonstrated that low testosterone levels may be associated with OSA [93].…”
Section: Obstructive Sleep Apnea Syndromementioning
confidence: 91%